Effects of soil enrichment, watering and seedling age on establishment of Mediterranean woody species (Acta Oecologica, 2010)
Vegetation restoration in strongly degraded lands has inherent limitations. Among the most relevant limitations in Mediterranean Mountains are severe drought and stressful levels of irradiance during summer. Thus, it is common that seedlings planted in open ground incur high rates of early mortality. In the context of a project of restoration of a burned area in Southern Spain, we evaluate the efﬁciency of watering and enrichment with native soil, and the inﬂuence of seedling age on survival and growth of 9 late-successional tall shrubs and trees planted in open ground. We also explore how small-scale variation in environmental variables relates to establishment success. Our results show an overall positive effect of watering on the survival of planted seedlings, while the effects of enrichment with native soil and age of planted seedlings were species-speciﬁc. Seedling establishment varied markedly with the presence of ravines, which duplicated seedling survival. This suggests that ravines may be more easily restored, improving their role as corridors in landscape designs of restoration. Independently of the treatment applied, Rosa sp. and Crataegus monogyna, both ﬂeshy-fruited species, had the highest rates of establishment. In conclusion, this study shows the viability of low aggressive restoration techniques to assist vegetation recovery in ﬁre-degraded environments. Speciﬁcally, watering and planting in ravines should be considered where restoration practices are applied in areas lacking vegetation cover. Some species highly attractive for animal dispersers and of easy establishment (Rosa sp. and Crataegus sp.) could be used to enhance spontaneous regeneration within and beyond corridors through increasing seed attraction and dissemination.